Microwave ablation is as effective as radiofrequency ablation for very‐early‐stage hepatocellular carcinoma. Issue 1 (19th January 2017) - Xu, Yun; Shen, Qiang; Wang, Neng; Wu, Pan‐Pan; Huang, Bin; Kuang, Ming; Qian, Guo‐Jun
Abstract: Background: Percutaneous radiofrequency ablation (RFA) is a first‐line treatment for very‐early‐stage hepatocellular carcinoma (HCC), whereas the efficacy of percutaneous microwave ablation (MWA) for very‐early‐stage HCC remains unclear. The purpose of this study was to clarify this issue by comparing the safety and efficacy of percutaneous MWA with percutaneous RFA in treating very‐early‐stage HCC. Methods: Clinical data of 460 patients who were diagnosed with very‐early‐stage HCC and treated with percutaneous MWA or RFA between January 2007 and July 2012 at the Eastern Hepatobiliary Surgery Hospital, The Second Military Medical University, in Shanghai, China were retrospectively analyzed. Of these 460 patients, 159 received RFA, 301 received MWA. Overall survival (OS), recurrence‐free survival (RFS), local tumor progression (LTP), complete ablation, and complication occurrence rates were compared between the two groups, and the prognostic factors associated with survival were analyzed. Results: No significant differences were observed between the two groups in terms of the 1‐, 3‐, or 5‐year OS rates (99.3%, 90.4%, and 78.3% for MWA vs. 98.7%, 86.8%, and 73.3% for RFA, respectively; P = 0.331). Furthermore, no significant differences were observed between the two groups in terms of the corresponding RFS rates (94.4%, 71.8%, and 46.9% for MWA vs. 89.9%, 67.3%, and 54.9% for RFA, respectively; P = 0.309), the LTP rates (9.6% vs. 10.1%, P = 0.883), the complete ablation rates (98.3% vs. 98.1%, P = 0.860), or the occurrence rates of major complications (0.7% vs. 0.6%, P = 0.691). By multivariate analysis, LTP, antiviral therapy, and treatment of recurrence were independent risk factors for OS ( P < 0.001), and the alpha‐fetoprotein level was an independent prognostic factor for RFS ( P = 0.002). Conclusions: MWA is as safe and effective as RFA in treating very‐early‐stage HCC, supporting MWA as a first‐line treatment option for this disease.